Designing RME-based linear equation lesson oriented to mathematical creative thinking and disposition - Yudha, Adinda Salshabilla; Wijaya, Ariyadi (Jurnal Gantang, 2026)
Mathematical creative thinking (MCT) is an essential 21st-century competency and is closely related to mathematical disposition (MD). However, both remain underdeveloped due to ineffective instructional designs. This study reports the development and validity of Realistic Mathematics Education (RME)-based instructional materials on one-variable linear equations (O-VLE) for seventh-grade students, integrating MCT and MD simultaneously. The study follows the McKenney and Reeves development research model, consisting of analysis & exploration, design & construction, and evaluation & reflection. The analysis phase revealed that Indonesian junior high school students generally demonstrate low MCT, partly due to weak mathematical disposition and procedural, rote-based algebra instruction. Therefore, meaningful learning was designed using RME with an edutainment context. The instructional materials were developed based on four MCT indicators (fluency, flexibility, originality, and elaboration) and six MD indicators (curiosity, enthusiasm, tenacity, self-confidence, willingness to share, and appreciation of mathematics). Expert judgment confirmed that both the teaching module and student worksheet achieved high validity. Future research will evaluate the practicality and effectiveness of the developed instructional materials through classroom implementation.